Hospitality Business Success: The Vital Role of Human Resource Training in The Digital Era - Muhammad, A Fadel; Devi, Ni Nyoman; Goeliling, Ardiansyah; Arimbawa, I Gede Arya Pering; Amin, Abdul Rahim (PT. Maju Malaqbi Makkarana, 2023)
Human resource management (HRM) in the hospitality industry is a key element to achieving success and providing quality service to guests. HR management covers various aspects, including career planning, development, training, compensation, and performance appraisal. This research uses a qualitative approach in a descriptive research type to understand the important role of HR in the hospitality industry. Career planning and employee development help motivate and maintain employee morale, while ensuring placements that match their competencies and goals. Fair and sustainable compensation is an important factor in maintaining employee satisfaction and motivating them to perform. Performance appraisals help identify employees' strengths and weaknesses and provide the necessary feedback for improvement. In the competitive hospitality industry, effective HR management is the key to success in delivering superior service and achieving long-term business goals. This research provides insight into the importance of HR management in the hospitality industry in the digital era.